An Analysis on The Development of E-Students Worksheet (E-LKPD) by Using Liveworksheet in Writing Hortatory Exposition Text - Amalyasari, Maya; Marsha Firio Armaditya; jazuli (ANFA MEDIATAMA, 2023)
This study aims to analyze the development of E-LKPD in writing hortatory exposition text. Along with technology development, LKPD evolved into printed teaching material that could be presented in electronic media. The teacher gave the students an assignment with an ordinary LKPD. So that, the students felt bored. In this research, the researcher analyzed a teaching material that was an E-LKPD. The subject of the research was 11th-grade or 2 senior high school students. The research was taken on the English students in the 2022/2023 school year. The research method used was descriptive qualitative. The researcher decided to do an analysis of the implementation of E-LKPD in writing hortatory exposition text. The research was conducted in SMA Taman Harapan Kota Malang. The following techniques were used to analyze the data: recording the appearance of significant events, followed by interpretation of the results. The data collection technique in this research was used questionnaire and documentation. The analysis of students' responses highlights the benefits of using E-LKPD with liveworksheet in English learning. These tools enhance engagement, accessibility, and effectiveness, resulting in better learning outcomes, higher student motivation, and improved comprehension. Students strongly endorse the integration of these technologies in their English education. using E-LKPD with liveworksheet media to enhance English learning by providing engaging and accessible content while emphasizing the importance of proper facility utilization and its potential benefits for Industry 4.0 education.